2009
DOI: 10.1159/000260083
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Study of Grass Allergen (Lol p 1) in Different-Sized Particles

Abstract: Background: The Poaceae family is considered one of the main causes of pollen allergy in industrialized countries. The aim of this study is to establish the dynamics of the Poaceae allergens and determine their distribution in the different-sized particles in the atmosphere. Methods: The air of Granada (southern Spain) was sampled during the pollination period of Poaceae using a cascade impactor and a Hirst-type volumetric collector simultaneously. The sampled airborne allergens were analyzed by indirect ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 84 publications
8
28
1
4
Order By: Relevance
“…In support, De Linares et al (11) revealed that allergenic activity of Ole e 1 in the atmosphere primarily involves paucimicronic particles. The release of paucimicronic and submicronic particles containing allergens into the atmospheric aerosol has been described for other pollen species including grasses, weeds, and trees (4)(5)(6)(7)(8)(9)(10)12). These particles include mainly starch granules, polysaccharide particles, and other subpollen particles that are scarce or absent in olive pollen (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support, De Linares et al (11) revealed that allergenic activity of Ole e 1 in the atmosphere primarily involves paucimicronic particles. The release of paucimicronic and submicronic particles containing allergens into the atmospheric aerosol has been described for other pollen species including grasses, weeds, and trees (4)(5)(6)(7)(8)(9)(10)12). These particles include mainly starch granules, polysaccharide particles, and other subpollen particles that are scarce or absent in olive pollen (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several works have reported that allergen liberation from pollen grains occurs in two different compartments: first, outside the individual organism when pollen grains are spreading through the atmosphere; and second, on the mucosal surface of the upper respiratory tract after inhaling pollen. Previous studies have shown that the air, in addition to carrying airborne pollens, contains allergenic pollen-derived submicronic (,10 mm) and paucimicronic (,1 mm) particles that can reach the lower airways, eliciting allergic symptoms in susceptible subjects (4)(5)(6)(7)(8)(9)(10)(11)(12). These particles are mainly composed of starch granules and polysaccharide particles, structures that are scarce or absent in mature olive pollen (13).…”
mentioning
confidence: 99%
“…In addition, real-time data on both weather forecasting and pollination are not available in many countries at present. Finally, despite the increasing amount of data about allergen content of ambient air published in recent years [34,35], to date, pollens or mould allergens have never been quantified during a thunderstorm. Hopefully, availability of pollen allergen count on a daily basis, as is planned in the frame of the European HIALINE project (www.hialine.eu), could provide conclusive data on the actual changes in the allergenic load of the air during such an extreme precipitative event.…”
Section: Public Health Dimensionmentioning
confidence: 99%
“…However, humans react to the allergen and the concentration of airborne pollen (the pollen count) is a proxy of exposure. Indeed, several investigations imply that the pollen count might not be representative for allergen exposure, also because allergen was found in non-pollen bearing fractions of ambient air (Schäppi et al, 1997b;De Linares et al, 2010;Fernandez-Gonzalez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%